2010
DOI: 10.1097/tp.0b013e3181f28bb0
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival of Composite Hemiface/Mandible/Tongue Allografts Correlates With Multilineage Chimerism Development in the Lymphoid and Myeloid Compartments of Recipients

Abstract: We introduced a new multitissue model of composite hemiface/mandible/tongue allograft containing lymphoid and vascularized BM components. Long-term allograft survival correlated with development and maintenance of donor-specific chimerism in lymphoid organs and BM compartment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…Recently, it has been proposed that VBMT may be superior to bone marrow cell transplantation for the establishment of chimerism and the induction of tolerance. Several studies have suggested that femoral, sternal, mandibular elements within the allograft may serve as a substantial source of bone marrow cells, resulting in the development of donor-specific chimerism [11], [21], [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been proposed that VBMT may be superior to bone marrow cell transplantation for the establishment of chimerism and the induction of tolerance. Several studies have suggested that femoral, sternal, mandibular elements within the allograft may serve as a substantial source of bone marrow cells, resulting in the development of donor-specific chimerism [11], [21], [22].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that vascularized bone marrow transplantation (VBMT) may be superior to conventional bone marrow cell transplantation for the induction of tolerance. This phenomenon is thought to be associated with the bone components, which serve as a vascularized method of delivering donor-origin stem and progenitor cells [10], [11]. However, the exact mechanism remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Monotherapy protocol with CsA has been applied in many experimental VCA models including models with a single component of allograft (skin) and in more complex models such as limb and face allografts [923]. …”
Section: Monotherapy Protocol With Calcineurin Inhibitors For Chimmentioning
confidence: 99%
“…Indeed, infusion of BM-derived cells from HDODs, as an adjuvant therapy, can induce specific immunological tolerance of the transplanted organ (25)(26)(27). Thus, Cirocco et al (28) observed that renal recipients had significantly lower rates of chronic rejection and higher graft survival compared with equivalent non-infused controls.…”
Section: Discussionmentioning
confidence: 95%